Double skin rubberized steel fiber mixed composite column. (2022) - Manisha, S.; Vinoth, S.; Suresh Shunmugaraj, M.; Manoj Kumar, M.; Pavithra Yadav, Yanamala
Abstract: Concrete-filled steel tubular (CFST) columns provide a number of structural advantages, such as high strength and fire resistance, good ductility, and huge energy absorption capabilities. ANSYS is used to investigate the structural performance of a double skin rubberized steel fiber mixed composite column. The column incorporated concrete's compressive strength as well as steel's tensile strength. The performance of rubberized steel fiber mixed concrete is initially assessed. To improve the damping property and stop the vibration, 20mesh crumb rubbers are employed. Crumb rubbers are substituted in various proportions (5 percent, 10%, 15%, and 20%) with fine aggregate. Steel fibers are used at a 0.75 percent concentration to reduce fracture diffusion and to sustain dynamic and static loads. Compressive strength, splitting tensile strength, and flexural strength tests are all performed. Crumb rubber replacement enhances compression strength, split tensile strength, and flexural strength up to 15%, after which the strength tends to decline, therefore it is determined that crumb rubber replacement up to 15% and steel fiber 0.75 percent can be used. Various types of columns are modelled and their structural performance loads are studied Hexagonal in square (HS), Hexagonal in circular (HC), and Hexagonal in Hexagonal (HH). When compared to traditional reinforced concrete (RC) columns, CFST columns are more cost-effective, faster to construct, and can handle higher loads. ANSYS is used to apply an axial load on the above columns and analyze them (finite element method). Finally, the outcome is compared to various column portions. When compared to HS and HH columns, the HS column has double the weight bearing capability.